2001
DOI: 10.1002/etc.5620200608
|View full text |Cite
|
Sign up to set email alerts
|

Tumor prevalence and biomarkers of exposure in brown bullheads (Ameiurus nebulosus) from the tidal Potomac River, USA, watershed

Abstract: Associations between contaminant exposure and liver and skin tumor prevalence were evaluated in brown bullheads (Ameiurus nebulosus) from the tidal Potomac River, USA, watershed. Thirty bullheads (> or = age 3) were collected from Quantico embayment, near a Superfund site that released organochlorine contaminants; Neabsco Creek, a tributary with petroleum inputs from runoff and marinas; and Anacostia River (spring and fall), an urban tributary designated as a Chesapeake Bay region of concern, that was contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
4
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 32 publications
6
69
4
1
Order By: Relevance
“…Such an observation is not unexpected and most likely reflects normal shifts in reproductive physiology, and has been reported previously (Yang et al 2006). While increased HSI has been used as an indicator of contaminant-associated (Fabacher and Baumann 1985;Pinkney et al 2001), this biomarker did not support evidence of differences between rivers in the present study. Reduced condition factor (Ktl) in wild species inhabiting ecosystems contaminated with organochlorines have been previously reported (Rocha and Monteiro 1999;Anderson et al 2003).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Such an observation is not unexpected and most likely reflects normal shifts in reproductive physiology, and has been reported previously (Yang et al 2006). While increased HSI has been used as an indicator of contaminant-associated (Fabacher and Baumann 1985;Pinkney et al 2001), this biomarker did not support evidence of differences between rivers in the present study. Reduced condition factor (Ktl) in wild species inhabiting ecosystems contaminated with organochlorines have been previously reported (Rocha and Monteiro 1999;Anderson et al 2003).…”
Section: Discussioncontrasting
confidence: 75%
“…Skin tumors, including papillomas and squamous cell carcinomas have been used as indicators of chemical exposure in brown bullhead and other species (Grizzle et al 1981;Smith et al 1989;Black and Baumann 1991;Pinkney et al 2001;Blazer et al 2009a). Although no cause-and-effect correlations have been made in wild populations, papillomas have been experimentally induced in brown bullhead by repeated dosing of the skin with sediment extracts with high levels of PAHs (Black et al 1985).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, for S. jello, Vijayakumar et al (2014) reported a prevalence of 12.1%, which was much higher than the overall prevalence of 0.37% that we found among S. jello. Sex can be an important factor in tumour prevalence in fish, with females at higher risk than males (Baumann et al 1990, Pinkney et al 2001, 2004. In the present study, we observed a higher incidence among females than among males.…”
Section: Discussionsupporting
confidence: 57%
“…Numerous studies have documented elevated levels of chemical contaminants in sediments, surface waters and fish tissue throughout the river (Foster et al 2000;McGee et al 2009;Velinsky et al 1994;Wade et al 1994) and their impact to fish and benthic biota (McGee et al 2009;Pinkney et al 2004;Schlekat et al 1994;Velinsky and Cummins 1996). In the past decade, the District of Columbia and State of Maryland have implemented assessments and control programs that are geared to reducing the inputs of many contaminants and begin to restore the river.…”
Section: Introductionmentioning
confidence: 96%